Diabetes and Its Complications 2018
DOI: 10.5772/intechopen.70668
|View full text |Cite
|
Sign up to set email alerts
|

Fine Particulate Matter (PM2.5) Air Pollution and Type 2 Diabetes Mellitus (T2DM): When Experimental Data Explains Epidemiological Facts

Abstract: Epidemiologic and experimental studies suggest that environmental exposures to air pollutants can increase prevalence of metabolic and cardiorespiratory diseases. Among the risk factors, many studies have shown that air pollution, especially by fine particulate matter (PM 2.5), can lead to the development of type 2 diabetes mellitus (T2DM) or make diabetics more susceptible to other health complications. This chapter aimed to discuss the pathophysiologic mechanisms evolved in susceptibility to cardiorespirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…head tracheobronchial (TB) and pulmonary region 9,10 and cause several disorders like asthma, chronic obstructive pulmonary disease, and even cancer 7 Further it also causes Cardiopulmonary mortality and metabolic disorder like diabetes. 11,12 The deposition of particulate matter inside the human body depends on the duration of exposure to particulate matter in ambient air in addition to various other factors such as nostril shape, weight, age, gender, ventilation, and exercise level. 13 Inhalation of ultrafine particles deposited in the lungs can cause alveolar inflammation and several hematological disorders like coagulation of blood, plasma viscosity, fibrinogen, plasminogen activator inhibitor, can not only cause cardiovascular diseases but can also cause inflammatory reactions.…”
Section: Introductionmentioning
confidence: 99%
“…head tracheobronchial (TB) and pulmonary region 9,10 and cause several disorders like asthma, chronic obstructive pulmonary disease, and even cancer 7 Further it also causes Cardiopulmonary mortality and metabolic disorder like diabetes. 11,12 The deposition of particulate matter inside the human body depends on the duration of exposure to particulate matter in ambient air in addition to various other factors such as nostril shape, weight, age, gender, ventilation, and exercise level. 13 Inhalation of ultrafine particles deposited in the lungs can cause alveolar inflammation and several hematological disorders like coagulation of blood, plasma viscosity, fibrinogen, plasminogen activator inhibitor, can not only cause cardiovascular diseases but can also cause inflammatory reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) reports that long exposure to PM 2.5 can generate respiratory and cardiovascular problems [9]. PM is also responsible for diabetes [10], ischemic heart disease and respiratory infection [11]. Moreover, [12] has shown that PM deposition in the respiratory system is higher in the alveolar region followed by the nasal and tracheobronchial region.…”
Section: Introductionmentioning
confidence: 99%
“…head tracheobronchial (TB) and pulmonary region 9,10 and cause several disorders like asthma, chronic obstructive pulmonary disease, and even cancer 7 Further it also causes Cardiopulmonary mortality and metabolic disorder like diabetes. 11,12 The deposition of particulate matter inside the human body depends on the duration of exposure to particulate matter in ambient air in addition to various other factors such as nostril shape, weight, age, gender, ventilation, and exercise level. 13 Inhalation of ultrafine particles deposited in the lungs can cause alveolar inflammation and several hematological disorders like coagulation of blood, plasma viscosity, fibrinogen, plasminogen activator inhibitor, can not only cause cardiovascular diseases but can also cause inflammatory reactions.…”
Section: Introductionmentioning
confidence: 99%